Rancang Bangun GPS Tracker di Kapal dengan Menggunakan Internet of Things (IoT) - Muchammad Muzammil Arrozak; Antonius Edy Kristiyono; Prihastono Prihastono (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to design and develop a GPS tracking system for ships integrated with Internet of Things (IoT) technology. The system enables real-time ship position monitoring via the Telegram application by utilizing ESP32, SIM800L, and GPS Neo 6M modules. The research employs an experimental method with both static and dynamic testing of hardware components such as GPS modules, SD cards, and battery performance. The test results demonstrate that the system successfully transmits accurate coordinate data to Telegram and logs the location on the SD card module. This system is expected to serve as an alternative solution to improve ship tracking security and efficiency, particularly in emergency situations or AIS signal loss.